Analisis Multiplier Effect Program Makan Bergizi Gratis (MBG) terhadap Penciptaan Lapangan Kerja di Kecamatan Batang Kuis, Deli Serdang (Tinjauan Maslahah) - Hamni Lubis, Namira; Qarni, Waizul; Marliyah Marliyah (Jurnal Riset Akuntansi, 2025)
The Free Nutritious Meal Program (MBG) is a national public policy that is not only oriented towards fulfilling community nutrition, but also has a local economic impact through the involvement of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the multiplier effect of MBG on job creation in Batang Kuis District, Deli Serdang Regency and review it from the perspective of maslahah in Islamic economics. The research method uses a qualitative approach with field studies through observation and interviews with the managers of the Nutrition Fulfillment Service Unit, operational workforce, and local MSME actors. The results of the study show that MBG is able to create direct jobs, such as operational personnel, and indirectly through increasing demand for MSME products. In addition, this program strengthens the local economic turnaround by involving community-based supply chains. From an Islamic economic perspective, MBG contains the value of maslahah because it supports hifz al-nafs through the fulfillment of community nutrition and hifz al-mal through improving economic welfare. Thus, MBG not only becomes a nutrition policy instrument, but also serves as a strategy for local economic empowerment that is in line with Islamic economic principles.